Molecular Pathways: Targeting the kinase effectors of RHO-family GTPases - Prudnikova, Tatiana Y. (Clin Cancer Res, 2014)
RHO GTPases, members of the RAS superfamily of small GTPases, are adhesion and growth-factor activated molecular switches that play important roles in tumor development and progression. When activated, RHO-family GTPases such as RAC1, CDC42, and RHOA, transmit signals by recruiting a variety of effector proteins, including the protein kinases PAK, ACK, MLK, MRCK, and ROCK. Genetically-induced loss of RHO function impedes transformation by a number of oncogenic stimuli, leading to an interest in developing small molecule inhibitors that either target RHO GTPases directly, or that target their downstream protein kinase effectors. Although inhibitors of RHO GTPases and their downstream signaling kinases have not yet been widely adopted for clinical use, their potential value as cancer therapeutics continues to facilitate pharmaceutical research and development and is a promising therapeutic strategy.